ASSESSMENT OF DNA STRAND BREAKS AND TOTAL ANTIOXIDANT STATUS IN TYPE 2 DIABETIC PATIENTS WITH AND WITHOUT COMPLICATIONS- A CASE-CONTROL STUDY - K, NITHYA; W, Isabel; T, Angeline; As, Priscilla; Aj, Asirvatham (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Objective: To evaluate the total antioxidant status (TAS) and the extent of DNA strand breaks (damage) as a measure of oxidative stress biomarkers in Type 2 diabetic patients (with and without complications) and controls. Materials and Methods: Blood samples were collected from 200 patients with type 2 diabetes mellitus (n=100 with complications and n=100 without complications) and 100 healthy individuals. Oxidative DNA damage was evaluated using alkaline single cell gel electrophoresis (comet assay). Total antioxidant status was assessed by Ferric Reducing Ability of Plasma (FRAP) assay. Results: TAS was found to be significantly lower in type 2 diabetic patients (with and without complications) compared to controls (p< 0.001). Â Similarly, patients with complications of type 2 diabetes mellitus had significantly lower TAS when compared to diabetic patients (p= 0.007). DNA damage analysis showed that the extent of damage was high in patients with diabetes mellitus (with and without complications) compared to controls (p< 0.001). Fasting glucose and glycosylated haemoglobin level (HbA1c) was found to be significantly higherin diabetic patients than controls (p< 0.05). Correlation analysis showed that there is no association between age, duration, sugar level, HbA1c, TAS and DNA damage in patients with Type 2 diabetes mellitus. Conclusion: Alterations in TAS and the extent of DNA damage was observed in patients with complications of diabetes mellitus indicate that oxidative stress is more in patients with complications when compared to patients without complications and healthy individuals. Therefore, further DNA damage and onset of complications in Type 2 diabetes mellitus could be prevented by counteracting the oxidative stress by therapeutic interventions using appropriate antioxidants. Key words: Hyperglycemia, Oxidative stress, DNA damage, Total antioxidant status, Type 2 diabetes mellitus, Vascular complication